Policies and Practices for Grading of Student Work in Distance and Online Learning System: A Survey of Teachers’ Perspective - Haleem, Bushra; Asghar, Sumbal (PJDOL, 2024)
Examining the current discussion on efficient grading practices in online and distance learning, a mixed-method study was designed to assess the grading policies and practices. Through census sampling, all of the education department's teachers as well as the head teachers of the Pakistani virtual university were chosen. In the questionnaire as research tool for this study, open and closed-ended questions about the learning outcomes, accuracy, and fairness of the grading scheme were developed by the researchers and approved by four experts prior to administration. The instrument's reliability was 0.89. The policy document was reviewed, and thematic analysis was done for open-ended question. Based on the results, majority of teachers were agreed that the grading schemes were accurate, fair, and measured learning outcomes. Additionally, the grading policies and the grading practices are aligned. However, there was a conflict between grading practice and policy in grading on curve. In addition to offering suggestions for creating an equitable, open, and engaging assessment system in online and distance learning, the findings may help administrators, instructors, and virtual universities to understand the advantages and disadvantages of the current grading procedures and help them optimize the assessment process in order to better support students’ learning and success.